The view of religious women of Iloilo City on the priesthood of women - De la Mota, Eileen Ledesma
This is a study on the view of religious women of Iloilo City on the priesthood of women. The study also describes and analyzes the views of Iloilo City's religious women on their situation in the Catholic Church as an institution. Focus Group Discussion (FGD) was used as the research method., The study reveals that the religious women of Iloilo City are happy about their situation in the Catholic Church and they view the latter as a very and effective institution. This also reveals that majority of the religious women of Iloilo City are not in favor on the priesthood of women. The study concludes by asserting that even though the religious women of Iloilo City are happy about their situation in the Catholic Church, they should be open to the priesthood of women so that females will be given the opportunity to follow their calling and have an opportunity at last to penetrate the male-dominated hierarchy of the Catholic Church. Part also of the conclusion of this study is the urging of the Catholics that it is time they should have a dialogue on the issue.